Funny As : the Story of New Zealand Comedy. - Horan, Paul (Auckland University Press, 2019)
From the Kiwi Concert Party to The Topp Twins, Billy T. James to Rose Matafeo, Fred Dagg to Flight of the Conchords, New Zealanders have made each other laugh in ways distinctive to these islands. The book takes us inside the comedy clubs, cabarets and television studios where comedians work; it charts the rise of cartoons and skits, parody and stand-up; it introduces us to how New Zealand's funniest men and women have made sense (and nonsense) out of this country's changing culture and society"--Publisher information.